Enhancing students’ performance in biology subject using an infographic digital flipbook - Mohd Sani, Rositi Mashani; Hamzah, Haliza; Ruslai, Nurulhidayati; Abdul Aziz, Nurul Azrina (Centre for Foundation Studies, International Islamic University Malaysia (IIUM), 2024)
Digital flipbook module is an innovation in 21st century teaching and learning that may replace the long wordy traditional method into fun, engaging, and effective learning experiences. The digital develop flipbook offers a comprehensive explanation of the learning material in the form of an interactive flowchart enabling the students to master the important keyword and sequential steps easily and effectively. The infographic digital Biology flipbook is expected to increase the student’s engagement, capture their attention and interest in Biology subjects as well as improve their performance in examinations. The objectives of this study are to identify the main categories that contribute to the effectiveness of using the digital flipbook, and to determine the effectiveness of digital flipbooks using iTa’LeEm through pre-test and post-test. This study focused on developing a flipbook module that consisted of 5 Biology chapters, followed by evaluation of students’ performance before (pre-test) and after accessing the flip book (post-test). A survey is administered to assess the effectiveness of the developed flipbook using the Likert scale. The statistical analysis conducted shows a significant improvement in students’ performance, understanding and learning experience in Biology subjects. Increased the mean score of pre test and post test from 75.90% (A-) to 87.10% (A). Hence, the study recommends the use of digital flipbook in Biology II subject as a learning material for biological sciences students in CFS IIUM, Gambang. Keywords. Digital flipbook modules, Biology subject, digital literacy, learning experience